1999
DOI: 10.1177/096368979900800606
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Embryonic Brain Cell Cytotoxicity Mediated by Human Natural Killer Cells

Abstract: Intracerebral transplantation of porcine embryonic dopamine-producing neurons has been suggested as a method to treat patients with Parkinson's disease. Even though the brain is an immunologically privileged site, neuronal xenografts are usually rejected within a few weeks. T cells are important for this process, but the exact cellular events leading to rejection are poorly characterized. Brain cells from ventral mesencephalon of 26-27-day-old pig embryos were used as target cells in flow cytometry-assessed cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Porcine microglia and endotheial cells express high amounts of DISCUSSION the α-Gal epitope (44), and recent evidence also suggests that α-Gal is present in small amounts on porcine Our results show that NK1.1+ cells are not important neurons (R. Barker, personal communication). It has mediators of the rejection process of porcine neural xebeen shown that humans have preformed antibodies nografts in mice.…”
Section: Flow Cytometry Stereological Methodsmentioning
confidence: 56%
See 3 more Smart Citations
“…Porcine microglia and endotheial cells express high amounts of DISCUSSION the α-Gal epitope (44), and recent evidence also suggests that α-Gal is present in small amounts on porcine Our results show that NK1.1+ cells are not important neurons (R. Barker, personal communication). It has mediators of the rejection process of porcine neural xebeen shown that humans have preformed antibodies nografts in mice.…”
Section: Flow Cytometry Stereological Methodsmentioning
confidence: 56%
“…This is in contrast to the situation for against at least two additional epitopes present on neural primarily vascularized organ xenografts, where NK cells tissue, and that NK cell-mediated antibody-dependent are crucial mediators of acute vascular rejection (33). In killing in vitro can take place in the absence of α-Gal this aspect, rejection of discordant secondarily vascularantibodies (44). Hence, the pig-to-mouse and the pig-toized cellular neural xenografts seems less complicated human in vivo xenograft combinations are not likely to than rejection of many other types of xenografts.…”
Section: Flow Cytometry Stereological Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The (PBMEC) might be highly immunogenic in the pig-tohuman situation, where the relationship between direct involvement of immunoglobulins (31,54), complement (1) (Larsson, Sumitran-Holgersson, Korsgren, Holgersand indirect antigen recognition is more balanced. In the present study, our aim was to determine whether son, and Widner, manuscript in preparation), natural killer (NK) cells (53), and NK T cells (29) in neural xeno-PBMEC could induce a human T-cell response via the direct pathway of antigen recognition. Resting PBMEC, graft rejection have also been suggested, as reviewed in Brevig et al (4).…”
Section: F]fluorodopa Uptake In Petmentioning
confidence: 99%